Respostas

A melhor resposta!
2014-06-20T15:25:33-03:00
F(x) = 54*x + 45

f(541) = substitui x por 541
f(541) = 54*541 + 45
f(541) = 29259


f(540) = substitui x por 540
f(540) = 54*540 + 45
f(540) = 29205

f(541) - f(540) 
29259 - 29205 =54

ou vc poderia fazer


(54*541+45) - (54*540 +45)\\\\(54*541+\not{45}-54*540-\not{45})\\\\54*541 - 54*540\\\\54(541-540)\\\\54*1 =54
4 4 4
2014-06-20T15:45:28-03:00
F(x)  = 54x + 45, logo:
a) f(541) = 54.(541) + 45 = 29259
b) f(540) = 54(540) + 45 = 29205
.....
f(541) - f(540) = 29259 - 29205 = 54
3 3 3